송전선로의 동기페이저를 이용한 고장점 표정장치 - 이경민(Kyung-Min Lee); 박철원(Chul-Won Park) (전기학회 논문지 P권, 65(1), 2016)
Fault location identification in the transmission line is an essential part of quick service restoration for maintaining a stable in power system. The application of digital schemes to protection IEDs has led to the development of digital fault locators. Normally, the impedance measurement had been used to for the location detection of transmission line faults. It is well known that the most accurate fault location scheme uses two-ended measurements. This paper deals with the complete design of a fault locator using GPS time-synchronized phasor for transmission line fault detection. The fault location algorithm uses the transmitted relaying signals from the two-ended terminal. The fault locator hardware consists of a Main Processor Unit, Analog Digital Processor Unit, Signal Interface Unit, and Power module. In this paper, sample real-time test cases using COMTRADE format of Omicron apparatus are included. We can see that the implemented fault locator identified all the test faults.